Pulmonary nodules detection assistant platform: An effective computer aided system for early pulmonary nodules detection in physical examination. (April 2022) - Han, Yu; Qi, Honggang; Wang, Ling; Chen, Chen; Miao, Jun; Xu, Hongbo; Wang, Ziqi; Guo, Zhijun; Xu, Qian; Lin, Qiang; Liu, Haitao; Lu, Junying; et al.
Highlights: The pulmonary nodule detection accuracy reaches 0.879 with an average of 1 false positive per CT for physical examination CT images, which is comparable to the experienced physicians. The detected nodules are classified into intrapulmonary nodules and pleural nodules to reduce the physician workloads, and classified into ground-glass opacity (GGO) nodules and non-GGO nodules to help doctor pay more attention to those suspected early lung cancer nodules. An effective CAD system for early pulmonary nodule detection and classification is built and has been on trial in hospital, which provides some detailed indicators for the detected pulmonary nodules. Abstract: Background and Objective: Early detection of the pulmonary nodule from physical examination low-dose computer tomography (LDCT) images is an effective measure to reduce the mortality rate of lung cancer. Although there are many computer aided diagnosis (CAD) methods used for detecting pulmonary nodules, there are few CAD systems for small pulmonary nodule detection with a large amount of physical examination LDCT images. Methods: In this work, we designed a CAD system called Pulmonary Nodules Detection Assistant Platform for early pulmonary nodules detection and classification based on the physical examination LDCT images. Based on the preprocessed physical examination CT images, the three-dimensional (3D) CNN-based model is presented to detect candidate pulmonary nodules and output detection results with quantitative parameters, the 3D ResNet is used to classify the detected nodules into intrapulmonary nodules and pleural nodules to reduce the physician workloads, and the Fully Connected Neural Network (FCNN) is used to classify ground-glass opacity (GGO) nodules and non-GGO nodules to help doctor pay more attention to those suspected early lung cancer nodules. Results: Experiments are performed on our 1000 samples of physical examinations (LNPE1000) with an average diameter of 5.3 mm and LUNA16 dataset with an average diameter of 8.31 mm, which show that the designed CAD system is automatic and efficient for detecting smaller and larger nodules from different datasets, especially for the detection of smaller nodules with diameter between 3 mm and 6 mm in physical examinations. The accuracy of pulmonary nodule detection reaches 0.879 with an average of 1 false positive per CT in LNPE1000 dataset, which is comparable to the experienced physicians. The classification accuracy reaches 0.911 between intrapulmonary and pleural nodules, and 0.950 between GGO and non-GGO nodules, respectively. Conclusion: Experimental results show that the proposed pulmonary nodule detection model is robust for different datasets, which can successfully detect smaller and larger nodules in CT images obtained by physical examination. The interactive platform of the designed CAD system has been on trial in a hospital by combining with manual reading, which helps doctors analyze clinical data dynamically and improves the nodule detection efficiency in physical examination applications.